Determination Of The Nearest Location Of Tourism In Semarang Regency With Proximity Analysis Method Based On Shortest Path Trace - Brian Krisnabel; Dewi Handayani (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2022)
Tourism in Semarang Regency is very diverse, such as historical building tours, culinary tours, and so on. These tourist sites are not close to each other so sometimes it makes tourists need to consider the choice of roads to get to each location in order to save time and gas. The many choices of roads to tourist destinations sometimes make tourists confused because they want to use the fastest route but don't know which routes should be used to get to tourist sites. This can be overcome by searching for a location with the shortest route to help tourists find the fastest route. By implementing a recommendation system, it can attract tourists to visit. Tourists can determine tourism objects based on location. This research utilizes proximity analysis algorithm with Shortest Path Trace to determine the closest travel route from the location of the application user to the tourist location. The Shortest Path Trace Algorithm used is based on mileage optimization calculations using Dijkstra's Algorithm. The implication of this research is that the application generated from this research can be used by tourists to find and find out the closest tourist location along with the shortest path to the tourist location.